RESTORATIVE JUSTICE FOR CHILDREN OF CYBER-PORN - Sina Iwi, Patricia; Yulianingsih, Wiwin (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
This study aims at finding out and analyzing the implementation of Restorative Justice for children of Cyber-porn offenders in the Sikka Regency Resort Police as well as to find out the obstacles and efforts in the implementation of Restorative Justice for children of Cyber-porn offenders. The type of this research is a type of empirical legal research that is descriptive and analytical. The type of data used in this study is peripheral data obtained through interviews with members of the Police Resort in Sikka district while secondary data uses primary legal materials, namely: Police regulation Number 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice, Law Number 11 of 2008 concerning Information and Electronic Transactions, Law Number 44 of 2008 concerning Pornography, Law Number 23 of 2002 concerning Child Protection and Law Number 11 of 012 concerning the Juvenile Justice System and for secondary legal materials and tertiary legal materials to support primary legal materials. Data collection is carried out by means of interviews and literature/documents. The technique used in this study uses qualitative analysis techniques. Cyber-porn crimes involving children, both perpetrators and victims in the community of Sikka Regency are still considered a disgrace so there are still many who do not want to report it to the police. In addition, investigators in implementing Restorative Justice are guided by Regulation of the Republic of Indonesia National Police Number 8 of 2021 concerning the Handling of Crimes Based on Restorative Justice, but in fact there are still many investigators who do not understand and master the application of Restorative Justice. Obstacles and efforts in the implementation of Restorative Justice for children of Cyber-porn offenders, especially in the community and Sikka Regency Resort Police officers.